1983
DOI: 10.1073/pnas.80.13.4069
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation of amplified DNA sequences from IMR-32 human neuroblastoma cells: facilitation by fluorescence-activated flow sorting of metaphase chromosomes.

Abstract: authors request that the following correction be noted. All hybrids described in Fig. 5 contained at least part of the human X chromosome, and the box for each hybrid in the column corresponding to the human X should have been darkened. This clerical error does not alter any conclusions in the paper.Proc. Natt Acad. Sci. USA Vol. 80, pp. A number of human tumors (1-3), in particular neuroblastomas (4-6), exhibit homogeneously staining chromosomal regions (HSRs) and extrachromosomal double minute objects (DMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
1

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 30 publications
(34 reference statements)
0
39
1
Order By: Relevance
“…The N-myc gene spans approximately 7 kb, whereas the size of the N-myc amplicon varies between 350 kb to over 1 Mb (Akiyama et al, 1994;Hiemstra et al, 1994;Kanda et al, 1983). Co-ampliÂźcation of otherÂŻanking genes, that may inÂŻuence disease progression, has been suggested (George et al, 1996;Squire et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The N-myc gene spans approximately 7 kb, whereas the size of the N-myc amplicon varies between 350 kb to over 1 Mb (Akiyama et al, 1994;Hiemstra et al, 1994;Kanda et al, 1983). Co-ampliÂźcation of otherÂŻanking genes, that may inÂŻuence disease progression, has been suggested (George et al, 1996;Squire et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Clone 8 is a 1.75 kilobase HindIII fragment previously isolated from the HSR of human neuroblastoma cell line IMR-32 (14). G2I is a cloned fragment from a cDNA library of IMR-32 cells and hybridized to EcoRI fragments of 6.6, 5.4, 4.0, 3.2 and 1.5 kilobases (18).…”
Section: Methodsmentioning
confidence: 99%
“…It is also intriguing that N- Kanda et al myc amplification was observed in diploid-or tetraploid-type neuroblastomas, but not in triploid-type tumors (13,16). Several sequences, which coamplify with N-myc have been isolated from neuroblastoma cell line IMR-32, and all mapped to the short arm of chromosome 2 (14,18).' Tumor DNA analysis, using these coamplified sequences as probe, apparently exhibited variation of amplicon size in the different tumors (300-3,000 kilobases) (25,26).…”
mentioning
confidence: 99%
“…One ofthe fibroblast donors was afemale carrier of the reciprocal X/13 translocation t(X;13)(q21-q23::q21-q31) (11). The hybrid cell lines have been characterized for human chromosome complements by isozyme and cytogenetic techniques (13,14) and with cloned DNA probes for each of the human autosomes and the X chromosome (15,16). DNAs prepared from somatic cell hybrids were digested with EcoRI, electrophoresed on 0.7% agarose gels, and subjected to Southern blot analysis.…”
mentioning
confidence: 99%